Inclusive Primary Schools Without Shadow Teachers: Can Learning Services be Optimal? - Arif Widodo; Umar Umar (Jurnal Educative: Journal of Educational Studies, 2020)
The Shadow Teacher is urgent in inclusive education. However, the shadow teacher cannot be found in all-inclusive educational institutions. The purpose of the study is to evaluate learning programs in inclusive primary schools that do not have Shadow Teachers. This case study was carried out in SDN Gunung Gatep, one of Central Lombok's inclusive elementary schools, from May to November 2020. The data was obtained through interviews with teachers, principals, and students with special needs. In addition to interviews, the data collection was taken by recording and observation during the learning process. Based on the results of the report, the teaching services provided by teachers are not satisfactory.Guru pendamping khusus berperan penting dalam pendidikan inklusif. Permasalahannya adalah tidak semua penyelenggara pendidikan inklusif memiliki guru pendamping khusus. Penelitian ini bertujuan untuk menganalisis layanan belajar di sekolah dasar inklusif yang tidak memiliki guru pendamping khusus. Pengambilan data dilaksanakan di SDN Gunung Gatep, salah satu sekolah dasar inklusif di Lombok Tengah, Â sejak Mei hingga November 2020. Data penelitian deskriptif kualitatif jenis studi kasus ini dilaksanakan melalui wawancara dengan informan utama guru, kepala sekolah dan siswa berkebutuhan khusus. Selain dengan wawancara, pengumpulan data dilakukan dengan dokumentasi dan observasi pada saat proses pembelajaran. Berdasarkan hasil penelitian, layanan belajar yang dilakukan guru belum optimal.